(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The clinical efficacy of immune checkpoint blockade (ICB) is often limited by the immunosuppressive tumor microenvironment (TME) and systemic toxicities. Liposomal nanocarriers offer a strategic platform for the targeted co-delivery of combinatorial therapies to overcome these barriers. Objective: To develop, characterize, and evaluate a novel PEGylated liposomal system (LP-Dox-aPDL1) for the co-encapsulation of doxorubicin (Dox) and an anti-PD-L1 nanobody (aPDL1) to achieve synergistic antitumor immunity. Methods: LP-Dox-aPDL1 was formulated via thin-film hydration and extrusion using a DPPC: Cholesterol: PEG-DSPE (60:35:5) lipid composition. Characterization included dynamic light scattering (DLS), transmission electron microscopy (TEM), and encapsulation efficiency (EE%) analysis. In vitro cytotoxicity was assessed against CT26.WT murine colon carcinoma cells using the MTT assay. Immune activation was measured via interferon-gamma (IFN-γ) and interleukin-12 (IL-12) release in a splenocyte co-culture model. In vivo antitumor efficacy and immune cell infiltration were evaluated in a syngeneic BALB/c mouse model bearing CT26 tumors (n=6 per group). Tumor volume was monitored, and immune cell populations were analyzed by flow cytometry. Results: LP-Dox-aPDL1 exhibited a hydrodynamic diameter of 115.4 ± 2.1 nm, a PDI of 0.18 ± 0.01, and high encapsulation efficiency for both Dox (88.5 ± 3.2%) and aPDL1 (92.7 ± 2.8%). In vitro, LP-Dox-aPDL1 demonstrated enhanced cytotoxicity (IC₅₀: 0.45 ± 0.07 µM) compared to free Dox (IC₅₀: 0.62 ± 0.09 µM; p < 0.05) and induced a significant 4.5-fold and 3.8-fold increase in IFN-γ and IL-12 secretion, respectively (p < 0.001). In vivo, LP-Dox-aPDL1 treatment resulted in a 78% reduction in final tumor volume (p < 0.001), with 2 out of 6 mice showing complete tumor regression. Flow cytometry revealed a 4.1-fold increase in tumor-infiltrating CD8⁺ T cells and a 3.2-fold decrease in myeloid-derived suppressor cells (MDSCs) compared to the PBS control (p < 0.001). Conclusion: The LP-Dox-aPDL1 platform successfully co-delivers a chemotherapeutic and an immunomodulator, demonstrating potent antitumor efficacy and favorable TME reprogramming. This study validates liposomal co-delivery as a promising strategy for enhancing cancer immunotherapy.